Perceptions and behaviors of Hispanic workers: a review. Issue 6 (5th August 2014) - Guerrero, Laura; A. Posthuma, Richard
Abstract : Purpose: – The purpose of this paper is to summarize research about Hispanic workers in the USA and identifies directions for future research. Design/methodology/approach: – The paper identifies, analyze, and summarize 112 peer reviewed publications that deal with Hispanic workers in the USA. Findings: – The findings are grouped into major categories that deal with prejudice, discrimination, and diversity; job-related attitudes and behaviors; job search and careers; the interface with gender, sexual harassment and work/family issues. The paper report the 53 most prevalent and well-supported findings. Research limitations/implications: – Given the paucity of research about Hispanics in the workplace, the conclusions derived from this literature review should be interpreted with caution. Originality/value: – A literature review of Hispanic workers in the USA has not been conducted to date. This review sets identifies the need for several areas of research in relation to Hispanic workers in the USA.